2022
DOI: 10.1093/emph/eoac013
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the evolution of SARS-CoV-2 under non-pharmaceutical interventions and testing

Abstract: Social and behavioral non-pharmaceutical interventions (NPIs), such as mask-wearing, social distancing, and travel restrictions, as well as diagnostic tests, have been broadly implemented in response to the COVID-19 pandemic. Epidemiological models and data analysis affirm that wide adoption of NPIs helps to control the pandemic. However, SARS-CoV-2 has extensively demonstrated its ability to evolve. Therefore, it is crucial to examine how NPIs may affect the evolution of the virus. Such evolution could have i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Before vaccines were widely accessible, strategies to control SARS-CoV-2 transmission and cases mainly relied on nonpharmaceutical interventions such as reducing social interactions, using antigenic testing, and imposing travel limits. Studies have shown declining lineage importations and persistence after lockdowns for the UK and Switzerland [5,11], and decreasing case numbers after establishment of NPIs [31][32][33][34]. To prepare for future pandemics and to identify the most effective measures, it is crucial to evaluate how SARS-CoV-2 lineage importations into the country and their subsequent internal dissemination relate to the nonpharmaceutical interventions that were put into effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before vaccines were widely accessible, strategies to control SARS-CoV-2 transmission and cases mainly relied on nonpharmaceutical interventions such as reducing social interactions, using antigenic testing, and imposing travel limits. Studies have shown declining lineage importations and persistence after lockdowns for the UK and Switzerland [5,11], and decreasing case numbers after establishment of NPIs [31][32][33][34]. To prepare for future pandemics and to identify the most effective measures, it is crucial to evaluate how SARS-CoV-2 lineage importations into the country and their subsequent internal dissemination relate to the nonpharmaceutical interventions that were put into effect.…”
Section: Discussionmentioning
confidence: 99%
“…Before vaccines were widely accessible, strategies to control SARS-CoV-2 transmission and cases mainly relied on nonpharmaceutical interventions such as reducing social interactions, using antigenic testing, and imposing travel limits. Studies have shown declining lineage importations and persistence after lockdowns for the UK and Switzerland [5,11], and decreasing case numbers after establishment of NPIs [31][32][33][34]. To The largest reductions of SARS-CoV-2 lineage importations were seen in Germany after the provision of free rapid tests, and the strengthening of regulations on mask wearing from wearing any kind of mask to obligatory surgical/FFP2 mask wearing in public transport and in stores, and on internal movements and gatherings.…”
Section: Discussionmentioning
confidence: 99%
“…NPIs have proven effective in reducing the spread of SARS-CoV-2 in many contexts [20][21][22][23][24][25] . The introduction of strong selection pressure by NPIs and the evolutionary impact of this has been the focus of much attention [26][27][28] , but how viral load dynamics are altered in vivo…”
Section: Main Textmentioning
confidence: 99%
“…NPIs have proven effective in reducing the spread of SARS-CoV-2 in many contexts [20][21][22][23][24][25] . The introduction of strong selection pressure by NPIs and the evolutionary impact of this has been the focus of much attention [26][27][28] , but how viral load dynamics are altered in vivo…”
Section: Main Textmentioning
confidence: 99%
“…NPIs have proven effective in reducing the spread of SARS-CoV-2 in many contexts 2025 . The introduction of strong selection pressure by NPIs and the evolutionary impact of this has been the focus of much attention 2628 , but how viral load dynamics are altered in vivo has not yet been explored. We were thus interested in the role of isolation as a strong NPI and explored the possible impact of such human behavioral changes on SARS-CoV-2 evolution.…”
Section: Main Textmentioning
confidence: 99%